2018
DOI: 10.5812/soj.64801
|View full text |Cite
|
Sign up to set email alerts
|

Inter and Intra-Observer Reliability of Dorr Classification in Proximal Femur Morphology

Abstract: Background: Proximal femur morphology determines the choice of cemented or uncemented Total Hip Arthroplasty (THR), and Dorr classification is widely used to type this characteristic. As a result, a considerable reliability for such typing system is expected. Objectives: The current study aimed at assessing inter and intra-observer reliability of Dorr classification in proximal femur morphology. Methods: A total of 50 standard hip radiographs from patients with trauma or THR candidates were evaluated by 6 obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Since CT scans are recommended before revisions, the patient would not be exposed to additional radiation. 39 The semi-automatic, numerical determination of femoral morphology, additionally improves the inter-and intraobserver reliability deplored in literature 29,30 Standard powered reaming appears to be superior compared to the manual approach since it is time-efficient, involves less physical work and yields to higher torsional strength, presumably due to a more uniform cavity. It is uncertain whether straight reamers further improve the junction due to their changed geometry or merely due to the sharper cutting edges caused by the less previous operating time of the reamer.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since CT scans are recommended before revisions, the patient would not be exposed to additional radiation. 39 The semi-automatic, numerical determination of femoral morphology, additionally improves the inter-and intraobserver reliability deplored in literature 29,30 Standard powered reaming appears to be superior compared to the manual approach since it is time-efficient, involves less physical work and yields to higher torsional strength, presumably due to a more uniform cavity. It is uncertain whether straight reamers further improve the junction due to their changed geometry or merely due to the sharper cutting edges caused by the less previous operating time of the reamer.…”
Section: Resultsmentioning
confidence: 99%
“…Since CT scans are recommended before revisions, the patient would not be exposed to additional radiation 39 . The semi‐automatic, numerical determination of femoral morphology, additionally improves the inter‐ and intraobserver reliability deplored in literature 29,30 and could be implemented fully automatically in modern preoperative planning software. The negative correlation between CCR and CI was already mentioned by Dorr et al but not pursued further 26 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mazhar et al performed a DI reliability analysis and stated that this resulted in moderate intra-observer and inter-observer agreements and stated that more reliable characterization systems are needed to classify femoral morphology [17]. In another study, inter-examiner reproducibility was found to be κ = 0.32 (fair agreement) in the inexperienced group and κ = 0.52 (moderate agreement) in the experienced group [18].…”
Section: Discussionmentioning
confidence: 99%